2003
DOI: 10.1159/000073992
|View full text |Cite
|
Sign up to set email alerts
|

Does Stress Influence Itching in Psoriatic Patients?

Abstract: Background: It is known that stress may exacerbate psoriasis. Pruritus is one of the most bothersome symptoms of psoriasis. Objective: The aim of this study was to evaluate if stress provokes itching in psoriatic subjects. Patients and Methods: 79 patients (44 males, 35 females) in an acute stage of psoriasis were included into the study. The severity of psoriasis was assessed by the Psoriasis Area and Severity Index (PASI). The psychosocial stress was measured by the Social Readjustment Rating Scale by Holmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 20 publications
4
49
0
2
Order By: Relevance
“…Moreover, a treatment with anti-histaminics rarely brings relief, and this seems to be connected with its sedative effect rather than with anti-histaminic properties (11). In our previous study we found that the presence and intensity of pruritus in patients with psoriasis may be related to perceived stress (14). Recently, Nakamura et al (15) demonstrated increased density of nerve fibres within the skin of psoriatic patients with pruritus compared with non-pruritic patients.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, a treatment with anti-histaminics rarely brings relief, and this seems to be connected with its sedative effect rather than with anti-histaminic properties (11). In our previous study we found that the presence and intensity of pruritus in patients with psoriasis may be related to perceived stress (14). Recently, Nakamura et al (15) demonstrated increased density of nerve fibres within the skin of psoriatic patients with pruritus compared with non-pruritic patients.…”
mentioning
confidence: 82%
“…All patients underwent careful dermatological examination: the severity of psoriasis was assessed according to the Psoriasis Area and Severity Index (PASI) (20) and pruritus intensity according to a standard Visual Analogue Scale (VAS) (II). Although the VAS is a highly subjective scale, it has been widely accepted for pruritus intensity assessment (18,21) and was also used by our group in previous studies on pruritus (11,13,14). Both disease severity and pruritus intensity were measured on the same day as blood sampling.…”
Section: Patients and Sample Collectionmentioning
confidence: 99%
“…The severity of depressive symptoms was rated based on the Beck's Depression Inventory (BDI) (14). The level of stress was measured within one month before disease exacerbation and was assessed according to the Holmes & Rahe Social Readjustment Rating Seale (SRRS) ( 15) as well as aeeording to the Stress Self-assessment Scale (no stress, mild, moderate, severe and extremely severe stress) (16). Detailed results of QoL, depression and stress have been published elsewhere (4,6).…”
Section: Other Psychological Assessmentsmentioning
confidence: 99%
“…PTSD-Symptome als Hautreaktionen manifestieren können [14]. Verschiedene Studien fanden eine Assoziation von Stress mit der Schwere der Hautkrankheit sowie der Häufigkeit und Intensität des Juckreizes [5,7,21,23]. Auch traumatische Ereignisse in der Lebensgeschichte scheinen einen Einfluss auf die Erkrankung zu haben.…”
unclassified